Mekanisme Kejayaan bagi Program Keusahawanan TVET dalam Kalangan Ibu Tunggal - Khalim, Nur Arina; Madar , Ahmad Rizal; Mohamad, Suhaimi (Research and Innovation in Technical and Vocational Education and Training, 2025)
Single mothers often face economic and social challenges such as financial constraints, psychological pressure, and a lack of support in balancing their roles as mothers and breadwinners. Entrepreneurship is seen as a solution to strengthen their economic position and improve the well-being of their families. This study aims to evaluate the effectiveness of the TVET entrepreneurship program in empowering single mothers in Muar, Johor. The main focus is to identify the levels of motivation, management skills, and interpersonal skills of participants, as well as to analyze the relationship between these three elements in the success of the program. A quantitative approach was used with a survey design and simple random sampling technique involving 191 single mothers. The primary instrument was a five-point Likert scale questionnaire. The data were analyzed using SPSS software through descriptive and inferential analysis, including Spearman correlation to identify relationships between variables. The findings show a significant increase in motivation, self-confidence, as well as skills in time management, finance, and marketing among the participants. Interpersonal skills such as communication and professional networking also improved. However, weaknesses still exist in the areas of risk and conflict management, which have been identified as areas for improvement. The TVET entrepreneurship program has a positive impact on the personal development of single mothers and has the potential to be an effective mechanism for economic empowerment. Improvements in the training modules, particularly related to risk management and complex communication, are needed to ensure the long-term success of participants in entrepreneurship.